Pengaruh E-Trust, E-WOM, Perceived Ease of Use dan E-Service Quality Terhadap Loyalitas Konsumen Generasi Z Pengguna ShopeeFood - Zulfa, Moch; Kusuma, Satria Yudha (Jurnal Ilmiah Penelitian Mahasiswa, 2023)
This study aims to determine the effect of E-Trust, E-Word of Mouth, Perceived Ease of Use and E-Service Quality variables on Consumer Loyalty. The data source used in this study was 100 Gen Z respondents using the ShopeeFood application which were taken by distributing questionnaires. The technique used in this study was purposive sampling with the following criteria: 1) Consumers who use the ShopeeFood application, 2) Use the ShopeeFood application at least 2x a month, 3) Respondents are aged between 18-26 years. The analytical tool used is multiple linear regression analysis with the help of SPSS software. The results of the study show that 1) E-Trust has a positive effect on Consumer Loyalty, 2) E-Word of Mouth has a positive effect on Consumer Loyalty, 3) Perceived Ease of Use has a positive effect on Consumer Loyalty, 4) E-Service Quality has a positive effect on Consumer Loyalty.Key Words: E-Trust, E-Word of Mouth, Perceived Ease of Use, E-Service Quality, Consumer Loyalty.